Wear Characteristics of ZA-27/Al2O3 Composites Processed by Centrifugal Casting: Experimental Investigation - Jyothi, P. N.; Jagath, M. C.; Channakeshavalu, K. (Techniques and Innovation in Engineering Research Vol. 5, 2023)
Wear properties of ZA-27/Al2O3 Composites manufactured using centrifugal casting technique were investigated. Operating factors like the reinforced alumina particle size (20–100µm), the specimen's distance from the pin-on disc apparatus's center (0–40 mm), the melt's melting temperature (450–6500C), the weight percentage of added alumina (5–25), the sliding speed (100–500 rpm), and the typical wear load (10–50 N) were focused. ZA alloys are much suitable for applications having higher load concentration at lower speeds. For the analysis, the Taguchi approach with the notation L25 was used. Normal wear load was observed to be one of the parameters that has the greatest impact on wear rate and the dry sliding wear of composites, followed by sliding speed, weight percentage of Al2O3, specimen position, particle size, and melting temperature.